Penyuluhan Psikologis Bagi Ibu Pasca Abortus: Dukungan Emosional Dan Kesehatan Mental - Khasanah, Uswatun; Mulia, Madepan; Susanti, Susanti (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Abortion is a profound experience of loss and can have serious psychological impacts on women, such as stress, depression, guilt, and anxiety. Unfortunately, the psychological aspects of post-abortion are often overlooked in primary health care. This community service project aims to provide psychological counseling to post-abortion mothers through an educational and counseling approach as a promotive-preventive effort to maintain mental health. The activity was held at Community Health Center X, District Y, for three days in July 2025, involving 20 participants who had a history of abortion within the past year. The methods used included group counseling, psychological counseling, open discussions, and the distribution of information modules. The results of the activity showed a significant increase in participants' knowledge regarding the importance of emotional support and psychological recovery strategies after abortion. Participants also reported increased feelings of acceptance and reduced emotional burden after participating in the group counseling sessions. This activity demonstrates that psychological counseling is an effective form of intervention that can support the mental recovery of post-abortion mothers and should be integrated into public health services.